(untitled) (American Journal of Islam and Society, 1997)
Pluralism has emerged as an important aspect of political life since the advent of liberal democracy. It is considered essential for the success of modem states. It indicates the existence of vaiious conflicting ideologies, conception .. values. and purposes of human life at a social level and the plurality of autonomous groups and organizations at a political level. The existence of modem tates and the uccessful operation of democracy depends upon how they accommodate ethno-cultural diversities within the broad framework of their social ethos and how they develop state mechanisms to safeguard the interests of all groups to ensure the well-being of the masses. The book under review describes, in a limited manner, the features and problems of pluralism in Southeast Asia. The region exhibits the traits of a plural society where different groups and communities live side by side, maintaining their separate identities. Cultural interaction and civilized dialogue take place without major tension. The countries of the region, particularly members of ASEAN, have concentrated their efforts on economic development and proceeded along the path of industrialization as a means to that. They have succeeded in their attempt and distinguished themselves from other countries in the continent ...